Personalised medicine, self-management and intimate technologies: a philosophical analysis - Zwart, Hub (Henry Stewart Talks, 2016)
Personalised medicine, Technologies, Consequences, Self-management, The We-genome, Literation / obliteration of life, Environome / Exposome / Epigenome, IPOP: the Snyderome, Genealogy